Called to account: financial frauds that shaped the accounting profession - Clikeman, Paul M. (Routledge, 2025)
"Called to Account traces the evolution of the global public accounting profession through a series of scandals leading to voluntary or mandated reforms. Ever entertaining and educational, the book describes some of the most audacious accounting frauds of the last 90 years, and identifies the accounting standards and legislation adopted as a direct consequence of each scandal. While retaining favorite chapters exposing the schemes of "Crazy Eddie" Antar and Barry "the Boy Wonder" Minkow, this fourth edition includes new material describing the accounting problems at Carillion, Wirecard and Luckin Coffee. Students will learn that financial fraud is a global problem, and that accounting reform is heavily influenced by politics. With discussion questions, and a chart mapping each chapter to topics covered in popular auditing textbooks, together with supplemental PowerPoints for instructors, Called to Account is the ideal companion for classes in auditing, fraud examination, advanced accounting, or professional responsibilities"--